Proses metakognitif siswa dalam menyelesaikan masalah matematika berdasarkan gaya belajar VAK (visual, auditori, dan kinestetik) - Lamowa, Rachmad Abubakar; Irawati, Santi; Subanji, Subanji (UNIVERSITAS NEGERI MALANG, 2022)
This study aims to describe students' metacognitive processes in solving mathematical problems based on the VAK (Visual, Auditory and Kinesthetic) learning style. The research method used in this research is descriptive qualitative. The research was conducted in the eighth grade of MTs Satu Atap Al-Hidayah on Jl. Pattimura Gg. VI No. 300 Gelonggong Temas, Batu City. Students are identified their learning styles through questionnaires and then given questions related to solving problems that are open-ended. Of the 15 students studied, there were three students with a visual learning style, three students with an auditory learning style and five students with a kinesthetic learning style. The results of the analysis show that the best metacognition process occurs in students with visual learning styles which are indicated by the achievement of the most indicators and followed by students with kinesthetic learning styles and then students with auditory learning styles. The results showed that the learning style did not significantly affect the students' metacognition process, but rather the understanding of the concept.